GUT MICROBIOTA FIRMICUTES AND BACTEROIDETES RATIO CORRELATED TO PROPIONATE IN OBESE SUBJECTS - Selly Mulyadi; Trilis Yulianti; Rizky Abdullah (Farmaka, 2020)
Gut microbiota (Firmicutes, Bacteroidetes and Akkermansia muciniphila) imbalance is related with obesity. In colon, this gut microbiota produces short chain fatty acid (SCFA), which is hypothesized has a correlation with obesity.  The study was aimed to confirm the correlation between gut microbiota (Firmicutes/Bacteroidetes ratio, Akkermansia muciniphila) and SCFA (acetate, propionate, butyrate) in obesity. Subjects were recruited from Jakarta and surrounding areas on January until April 2020 and the study design was observational study with cross sectional approach. The subjects were 46 men, aged 25-40 years old. Subjects were divided into 2 groups, those are obese group and normal group. Analysis of Firmicutes, Bacteroidetes and Akkermansia muciniphila was done using real time PCR, while analysis of SCFA was done using GC-MS. This study found that there was positive correlation between Firmicutes/Bacteroidetes (F/B) ratio and propionate (r = 0.406 dan p = 0.024) in obese subjects. Correlation between Akkermansia muciniphila and SCFA could not be concluded since Akkermansia muciniphila was not detected in most of samples collected. There was no difference on F/B ratio (p=0.284), acetate (p=0.763), propionate (p=0.579), butyrate (p=0.648), total SCFA (p=0.514) between obese and normal group, however SCFA tends to be higher in obese group, while F/B ratio tends to be higher in normal group. Some of results are in line with previous reports, but data contradict with previous report regarding proportion of gut microbiota between grups, and this is still controversional.